The Impact of vertical theories of harm on investor returns: An event study of US vertical mergers - Ralph Sonenshine; Seyni Da (Journal of Risk and Financial Management, 2022)
The welfare implications of vertical mergers have been a subject of disagreement for decades. Similar to horizontal mergers, economists need to weigh the efficiency gains relative to the market power concerns when considering the competitive effects of vertical mergers. However, in vertical mergers, regulators are also concerned with other potential harmful effects, such as input and customer foreclosure. Using an event style technique, this paper explores these vertical theories of harm by comparing the abnormal returns of acquirers, targets, and the two combined in vertical and horizontal mergers that were challenged by regulators as potentially anticompetitive. Our results indicate that abnormal returns to targets were similar between vertical and horizontal mergers, but the gains to targets relative to acquirers were far higher in vertical versus horizontal mergers (53.6% versus 39.5%). In addition, we found that exclusionary effects have a positive impact (0.24% of the dollar abnormal return) on the bargaining position of targets. In contrast, acquirers gain 0.45% and 0.39% of the dollar abnormal return relative to targets when the antitrust concern entails collusive effects or elimination of potential competition, respectively.
Keywords: 650; abnormal returns; collusion; event study; exclusionary effects; unilateral effects; vertical mergers